2020
DOI: 10.1186/s13027-020-00307-6
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus BART microRNAs in EBV- associated Hodgkin lymphoma and gastric cancer

Abstract: Background: EBV produces miRNAs with important functions in cancer growth, tumor invasion and host immune surveillance. The discovery of EBV miR-BARTs is recent, and most of their functions are still unknown. Nonetheless, some new studies underline their key roles in EBV-associated malignancies. Main body: In EBV-associated tumors, the expression profile of miR-BARTs varies according to the cell type, autophagic process and signals received from the tumor microenvironment. By the same way of interest is the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 77 publications
(86 reference statements)
0
37
0
Order By: Relevance
“…Attempts have just begun to explore the roles of BART miRNAs in CHL. 2 A previous report demonstrated the expression of BART 19-3p and 13-3p miRNAs in CHL, with no or low-level expression of the other BART miRNAs. 3 Interestingly, a recent study showed that BART miRNAs were present in EBV-negative B cells and non-B cells, indicating that BART miRNAs could be transferred to neighboring cells via exosomes, and it might alter tumor microenvironment of CHL.…”
mentioning
confidence: 93%
“…Attempts have just begun to explore the roles of BART miRNAs in CHL. 2 A previous report demonstrated the expression of BART 19-3p and 13-3p miRNAs in CHL, with no or low-level expression of the other BART miRNAs. 3 Interestingly, a recent study showed that BART miRNAs were present in EBV-negative B cells and non-B cells, indicating that BART miRNAs could be transferred to neighboring cells via exosomes, and it might alter tumor microenvironment of CHL.…”
mentioning
confidence: 93%
“…In particular, H. pylori dependent stimulation of IFN-γ secretion, one of the key pro-inflammatory cytokines associated with disease severity [ 31 ], is implicated in EBV reactivation and intestinal GC [ 20 ]. Moreover, EBV-driven epigenetic modifications are enhanced in the presence of H. pylori , specifically the Cag A secretory antigen, resulting in increased cellular proliferation [ 32 ]. Furthermore, EBV and H. pylori associated gastric inflammation persistently activates Th17 T-cells which promote severe gastritis and GC [ 33 35 ].…”
Section: Immune Mechanisms Of Gastric Cancer Pathogenesismentioning
confidence: 99%
“…In 1990, Burke et al detected the expression of Epstein-Barr virus (EBV) in gastric adenocarcinoma tissues by PCR. Since then, several reports have been published indicating that EBV expression can be detected in gastric cancer tissues [3][4][5] . The positive rate of EBV expression was basically stable and estimated at approximately 10% [3][4][5] .…”
Section: Main Bodymentioning
confidence: 99%
“…Since then, several reports have been published indicating that EBV expression can be detected in gastric cancer tissues [3][4][5] . The positive rate of EBV expression was basically stable and estimated at approximately 10% [3][4][5] . However, its role in gastric cancer and the identi cation of the speci c signaling molecules involved in the development of this disease remain unclear.…”
Section: Main Bodymentioning
confidence: 99%